DAMPAK PELUNCURAN CHATGPT TERHADAP RETURN SAHAM PERUSAHAAN PENDIDIKAN DI AMERIKA SERIKAT - Mahrusoh, Sofiyatul (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2024)
The practicality of using ChatGPT to assist with human tasks has led many students to prefer ChatGPT over subscribing to paid educational applications. This phenomenon has impacted not only the student community but also caused shifts in the financial market, particularly for companies providing academic tutoring services. However, research on this topic remains limited, highlighting the need for further investigation. This study aims to determine the impact of ChatGPT on the stock returns of companies in the education sector in the United States. This research employs a quantitative approach. The sample consists of 37 education sector companies listed on the NASDAQ and NYSE stock exchanges. The sample was selected using purposive sampling, and the data utilized is secondary data. The data analysis technique used is panel data regression analysis with a common effect model. The results of this study indicate that the launch of ChatGPT has a negative and significant impact on the stock performance of education companies. These findings contribute significantly to the literature, particularly within the framework of signaling theory, enhancing the understanding of stock market responses to innovations such as ChatGPT.